Naruszenie interesu PRL jako podstawa rewizji nadzwyczajnej - Piekarski, Mieczysław (Wydział Prawa i Administracji UAM, 1982)
The article is based on the analysis of the jurisdiction of the Supreme Court. It can be considered as a continuation and, at the same time, a supplement to the reflections of Kazimierz Piasecki published in this year's first edition (1, 1981) of this journal. Breach of State interest understood as a ground for the extraordinary appeal is a qualified form of the flagrant legal offence. Hence the flagrant offence against the law is a premise for the extraordinary appeal. The legislator however, has defined neither "the flagrant offence against the law", nor "the breach of State interest". The expectations that these notions would eventually be defined by the Supreme Court proved futile. The grounds for the extraordinary appeal filed in a concrete case should be each time separately evaluated by the Supreme Court. The exhaustive evaluation such as that allows to examine whether a court decision which was appealed against is infringing the law flagrantly enough to break the state interest at the same time.
Breach of State Interest as a Ground for the Extraordinary Appeal